Palimpsestes ou l’image au second degré : Gail Albert Halaban, Hopper Redux, et Laetitia Molenaar, Here comes the Sun [it is all right] - Helena LAMOULIATTE-SCHMITT (E-REA)
Two contemporary artists, the American photographer Gail Albert Halaban and the Dutch painter and photographer Laetitia Molenaar, have decided to use Edward Hopper’s paintings as the starting point of art projects. In order to create the Hopper Redux series, Gail Albert Halaban went to a small New England village, where she located sixteen houses originally painted by Edward Hopper in the 1920s, and she then endeavoured to photograph them from the same vantage points. Laetitia Molenaar, for her part, constructed an even more elaborate framework in the Here comes the Sun [it is all right] series, in which she staged some of Hopper’s most famous paintings before photographing them in cardboard miniature settings. As a result of the dialogue initiated by these two artists with one of the most famous representatives of twentieth-century American realism, numerous questions about intericonic relations can be raised. In Halaban’s case, we will see that iconic narrativity can be a way of expressing the contemporary artist’s subjectivity, and to go beyond the mere interplay with the poetic language of past images. As for Molenaar, the intermedial dimension of her meta-photographs raises numerous questions about the aesthetic object, the notion of representation, as well as pictorial and photographic technique.